Efficient bifunctional piezocatalysis of Au/BiVO4 for simultaneous removal of 4-chlorophenol and Cr(VI) in water - Wei, Yan; Zhang, Yiwen; Geng, Wei; Su, Hanrui; Long, Mingce (Applied catalysis. B, Environmental, 2019)
[Display omitted] •The piezoelectric effect of Au/BiVO4 is characterized by PFM measurements.•Au/BiVO4 is used as a bifunctional piezocatalyst for removal of pollutants in water.•Simultaneous removal of 4-chlorophenol and Cr(VI) is achieved by piezocatalysis.•H2O2 and OH induced mechanism on Au/BiVO4 piezocatalysis is proposed. Piezocatalysis induced by polarization of piezoelectric materials is considered as an emerging technology in environmental cleanup. In this work, a piezoelectric material, Au nanoparticles modified BiVO4 (Au/BiVO4) is synthesized and its piezoelectric response is observed by piezo-response force microscopy. Au/BiVO4 is used as a bifunctional piezocatalyst for simultaneous removal of 4-chlorophenol (4-CP) and hexavalent chromium (Cr(VI)) upon ultrasonic vibration, with 91% and 83% of removal efficiency in 120 min, respectively. The piezocatalytic performance of Au/BiVO4 increases with the increase of ultrasonic power and the decrease of pH. The main active species for 4-CP oxidation and Cr(VI) reduction are determined to beOH and H2O2, respectively, since a significant formation rate ofOH is estimated by a probe method, and a high amount of H2O2 accumulation is directly detected. This study provides understanding on the piezocatalysis mechanism and brings new insights for development of piezocatalysis for multifunctional environmental applications.